PENGARUH SUHU REAKSI DAN JUMLAH KATALIS PADA PEMBUATAN BIODIESEL DARI LIMBAH LEMAK SAPI DENGAN MENGGUNAKAN KATALIS HETEROGEN CaO DARI KULIT TELUR AYAM - Wendi, Valentinoh Cuaca, Taslim (Universitas Sumatera Utara, 2015)
Biodiesel is an alternative fuel for diesel engines consisting of the alkyl monoesters from vegetable oils or animal fats. Beef tallow waste is the non-edible raw material with low cost production and the availability is huge in the cattle production. The objective of the study was to utilize beef tallow waste for biodiesel production using solid oxide catalyst which derived from the industrial eggshells. The materials calcined with temperature 900oC and time 2 hours, transformed calcium species in the shells into active CaO catalysts.The oil contained high free fatty acid (FFA) content of 1.86%. The FFA content of the oil was reduced by acid-catalyzed esterification. The product from this stage was subjected to produce biodiesel. Transesterification process reacts oil and methanol to produce methyl ester and glycerol. The produced methyl ester on the upper layer was separated from the glycerol and then washed. Effect of various process variables such as amount of catalyst and temperature were investigated. The biodiesel properties like methyl ester content, density, viscosity, and flash point was evaluated and was found to compare well with Indonesian Standard (SNI). Under the best condition, the maximum yield of 82.43% beef tallow methyl ester was obtained by using 9:1 molar ratio of methanol to beef tallow oil at 55oC, for a reaction time 1.5 hours in the presence 3 wt% of CaO catalyst. The results of this work showed that the use of beef tallow is very suitable as low cost feedstock for biodiesel production.